KEMANDIRIAN BELAJAR ANAK TAHFIDZ AL-QUR’AN PADA MASA COVID-19 DI PKBM HARAPAN BANGSA DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Suci Salbillah; Said Suhil Achmad; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study examines the Learning Independence of Tahfidz Al-Qur'an Children during the Covid-19 Period at PKBM Harapan Bangsa Village Tarai Bangun District Tambang Kampar Regency and in Independent Learning there is confidence, discipline, initiative, responsibility and motivation. The purpose of this study was to determine the learning independence of tahfidz al-qur'an children during the Covid-19 period at PKBM Harapan Bangsa, Tarai Bangun Village, Tambang District, Kampar Regency. This type of research is descriptive with a qualitative approach, where the data collection process is carried out by interviewing 4 subjects, namely 3 core informants and 1 control informant, with documentation included. Based on the results of the interviews, the researchers suggested 5 indicators, namely: (1) self-confidence, (2) discipline, (3) initiative, (4) responsibility, (5) motivation. Key Words: Independent Learning, Tahfidz Al-Qur'an, PKBM